2020
DOI: 10.3390/sports8060078
|View full text |Cite
|
Sign up to set email alerts
|

Increased Liveliness of Trunk Muscle Responses in Elite Kayakers and Canoeists

Abstract: Trunk stability functions play an important role in sport and everyday movements. The aim of this study was to analyze trunk strength, trunk muscles onset of activity, and rate of electromyographic rise (RER) in the case of self-inflicted and unexpected trunk loading. Thirty-two healthy young adults (16 elite kayakers/canoeists and 16 non-athletes) were measured with a multi-purpose diagnostic machine. Trunk strength was assessed in standing position. Trunk muscles onset of activity and RER were assessed throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…After pre-experimentation, three contraction intensities of 0%, 30%, and 60% MVIC were selected in this study to explore the optimal intensity for effective ES activation. Trunk flexion produces greater lumbar extension forces than the neutral trunk position, but this is primarily a force produced by the hip extensors with less force being generated by the lumbar muscles ( CHOLEWICKI and VANVLIET, 2002 ; Kocjan and Sarabon, 2014 ) also found that the lumbar back muscles contributed most to spinal stability in neutral isometric extension exercises compared to flexion tests. In combination with our previous experiment ( Zhang et al, 2023 ), lumbar extension strength in the trunk hyperextension position was not as strong as in the trunk neutral position, and therefore we chose to perform IPTE in the trunk neutral position to assess lumbar extensor strength.…”
Section: Introductionmentioning
confidence: 97%
“…After pre-experimentation, three contraction intensities of 0%, 30%, and 60% MVIC were selected in this study to explore the optimal intensity for effective ES activation. Trunk flexion produces greater lumbar extension forces than the neutral trunk position, but this is primarily a force produced by the hip extensors with less force being generated by the lumbar muscles ( CHOLEWICKI and VANVLIET, 2002 ; Kocjan and Sarabon, 2014 ) also found that the lumbar back muscles contributed most to spinal stability in neutral isometric extension exercises compared to flexion tests. In combination with our previous experiment ( Zhang et al, 2023 ), lumbar extension strength in the trunk hyperextension position was not as strong as in the trunk neutral position, and therefore we chose to perform IPTE in the trunk neutral position to assess lumbar extensor strength.…”
Section: Introductionmentioning
confidence: 97%